Refractories for Aluminium: Electrolysis and the Cast House (Springer, 2015)
This book details the peculiarities of the requirements for refractories designed for aluminium metallurgical process: reduction, cast house, and anode production. The author describes requirements specific to the properties and structure of refractory materials that differentiate it from the refractories for ferrous metallurgy and other refractories. A comparison is drawn between the properties and structure of refractories and carbon cathode materials from different points of view: from the point of physical chemistry and chemistry interactions during the metallurgical process and from the point of design of reduction pots and furnaces with the aspect to the service life time of metallurgical aggregates.